A Tripartite Composite Incorporating Nitrogen-Doped Graphene Oxide, Polypyrrole, and Silica for Lithium-Ion Battery Anodes - Al-Bujasim, Mohammed; Gencten, Metin; Donmez, Koray B.; Arvas, Melih B.; Karatepe, Nilgun; Sahin, Yucel (ELECTROCHEMICAL SOC INC, 2024)
In this study, N-doped graphene oxide-polypyrrole-silica (NGO-PPy-SiO2) composite was employed as a possible anode in Li-ion batteries. The chronoamperometric technique was employed to synthesize NGO, and within this study two samples were produced, one characterized by a high polypyrrle content (N1) and the other by a low polypyrrle content (N2). N2 has the maximum initial discharge capacity of 785 mAh g-1 at 0.1 C, which is greater than N1's capacity of 501 mAh g-1. The initial coulombic efficiency of the first cycle is around 72%, whereas the ICE of N2 is approximately 60%. N1 demonstrates outstanding cycling performance for 100 cycles at high rate (10 C) with maintain capacity as 100% and coulombic efficiency of 100%, as well as extremely stable capacity during the cycling. N2 has a maintain capacity of approximate to 79% and excellent coulombic efficiency, however the capacity during cycling is not as stable as N1.
Keywords: HIGH-RATE CAPABILITY; NANOCOMPOSITE ANODES; CYCLIC VOLTAMMETRY; HIGH-ENERGY; PERFORMANCE; NANOSHEETS; NANOWIRES; CAPACITY; ELECTRODE; POLYMERS; Materials Science; Physics